FIKIH KOMPREHENSIF: SEBUAH PENDEKATAN DALAM STUDI ISLAM - Zaleha, Zaleha (Journal Analytica Islamica, 2019)
Abstract: The study of Islamic law has always moved dynamically following the times, this is whatled to the study of Islamic law to be an interesting phenomenon for Muslim academics. In a moretechnical level Islamic law is identified with fiqh which also grows in conjunction with the growth ofIslamic religion. The law is formed from the laws of the Koran, from the various laws that come out ofthe prophet. As a fatwa against a case, or an award against disputes, or an answer to a question. Thecomplication of the Fiqh laws in the first period is formed from the laws of God and its Apostles, andthe source is the Koran and the Sunnah. Using the study’s approach to the library of the followingdescriptions will explain in detail the comprehensive jurisprudence as an approach to Islamic studies.Keywords: Jurisprudence, Comprehensive, Islamic studies